Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/17518423.2017.1354091
|View full text |Cite
|
Sign up to set email alerts
|

Intensive strength and balance training with the Kinect console (Xbox 360) in a patient with CMT1A

Abstract: The encouraging results for balance and endurance justify further studies on videogame-directed activities in CMT1A children/adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Also, Tarakci et al (39) reported a significant balance improvement in children and adolescents with CP treated by using Nintendo-Wii-Fit balance board. Progress in balance, after neurorehabilitation with Xbox and Kinect, was also reported in a child with Charcot-Marie-Tooth disease (41).…”
Section: Gaming Technologies In Longitudinal Neurorehabilitation Trialsmentioning
confidence: 73%
See 1 more Smart Citation
“…Also, Tarakci et al (39) reported a significant balance improvement in children and adolescents with CP treated by using Nintendo-Wii-Fit balance board. Progress in balance, after neurorehabilitation with Xbox and Kinect, was also reported in a child with Charcot-Marie-Tooth disease (41).…”
Section: Gaming Technologies In Longitudinal Neurorehabilitation Trialsmentioning
confidence: 73%
“…Our search identified nine longitudinal studies as reported in Table 1 (34)(35)(36)(37)(38)(39)(40)(41)(42). According to the PEDro scores, one of the most interesting paper was the one by Choi et al (35), showing that children with chronic brain injury (including CP), treated by virtual reality and occupational therapy, significantly improved upper-limb dexterity functions, performance of daily activities, and forearm supination, as compared to the control group.…”
Section: Gaming Technologies In Longitudinal Neurorehabilitation Trialsmentioning
confidence: 99%
“…This includes physiotherapy to maintain joint mobility, to increase muscle strength, and to improve both postural control and endurance; the use of orthoses to enhance walking efficiency, and foot functional surgery (FS) to correct ankle deformities and to improve gait functionality. 2,[7][8][9][10][11][12][13][14][15] The real benefit to the surgical approach is in striving to restore the physiological tibiotarsal and foot joint biomechanics and the correct rockers of gait as best as possible. Surgical procedures have been progressively improving since the late 1970s, based also on the surgeon's personal preferences and schools of thought.…”
Section: Introductionmentioning
confidence: 99%
“…Pagliano et al proposed a videogame-directed exercise program targeting children and adolescents diagnosed with Charcot–Marie–Tooth disease type 1A (CMT1A) [ 10 ]; using an Xbox 360 console connected to the Kinect movement sensor, the Kinect videogame delivers directed physical exercise activities aimed at improving overall balance and endurance by improving limb strength in the ankle.…”
Section: Introductionmentioning
confidence: 99%